Increasing the Competitiveness of the Russian Hotel Enterprises under Modern Conditions - KOVALTCHUK, Andrey Pavlovich; BLINOVA, Ekaterina Arturovna; MILORADOV, Konstantin Aleksandrovich (Journal of Environmental Management and Tourism; Vol 8 No 2 (2017): JEMT Volume VIII Issue 2(18) Spring 2017DO - 10.14505//jemt.v8.2(18).13, 2017)
Current economic situation leads to increased competition in the Russian market of hotel services though stimulating Russian hotels to pay more attention to their competitiveness. The most promising directions of increasing competitiveness of Russian hotels is to increase the level of service and quality of hotel services. The article discusses the key ways of increasing competitiveness of hotel companies. Authors developed a system of indicators to measure the level of competitiveness of the hotel, methods and procedures for improving service quality. Authors developed the methodology and tools for its implementation, which will make it easier for hotels to monitor the economic situation, have an instrument to assess the condition of the hotel enterprises and to provide direction for strategic development. Practical experience of implementation of the developed methodology to analyze the state of hotel enterprises in the Moscow region of 3-4* category is analyzed. Recommendations on its application are given by authors.